Pengaruh Pengajar Terhadap Motivasi Siswa MI Kelas 4 dalam Pembelajaran Bahasa Arab - Yuni Kusumastutik; Jihan Alhanin Choir (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study explores the impact of teaching methods on student motivation in Arabic language learning for fourth graders at MI Al Huda. Data from questionnaires, interviews, and observations reveal that interactive and varied teaching methods, such as group discussions, language games, and project-based learning, significantly enhance student motivation. The use of technology, including multimedia and educational apps, also positively affects motivation by making lessons more engaging and relevant. However, challenges such as resource limitations and the need for consistent emotional support from teachers are noted. The findings underscore the importance of dynamic teaching strategies and technological integration in boosting student engagement and motivation.